An Empirical and Theoretical Literature Reviews on Creative Economy of Culinary in South Heritage Town Square of Surakarta Palace (Central Java, Indonesia) - Achmad, Nur; Murwanti, Sri; Purnomo, Siddiq; Sholahuddin, Muhammad (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Keraton Surakarta is one of the tourism destinations in Surakarta, Central Java. The southern side Keraton Surakarta looks rundown with quite untidy culinary street vendors and it was well-known as an area for night prostitution a decade ago. Previous research has already identified a mapping and economic potential of creative SMEs of culinary occupying in the Alun-Alun Kidul Keraton Kasunanan Surakarta. This literature and empirical study consists of three sections. First, it presents creative economic potential in the Alun-Alun Kidul Keraton Kasunanan Surakarta. Second, it discusses the various regulations on the management of street vendors. Third, it presents various empirical studies on the creative economy and the arrangement of the Alun-Alun Kidul. Content analysis of literature study was conducted to generate a pre-analysis strengths, weaknesses, opportunities and challenges of the creative economy in the Alun-Alun Kidul Keraton Kasunanan Surakarta. The results of this study show that the Alun-Alun Kidul Keraton Kasunanan Surakarta becomes a recreation potential for medium-small income people. Besides, the regulation issued by local government and the Kasunanan Surakarta prohibit it to be permanent place for street vendors. In addition, various empirical studies show the importance of managing and structuring the Alun-Alun Kidul Keraton Kasunanan Surakarta as small recreational place for public while accommodating street vendors leads to good and fair situation for all parties.